Дослідження впливу конструктивно-технологічних параметрів на процес прямого графітування електродів у печах Кастнера - Карвацький, Антон Янович; Панов, Євген Миколайович; Педченко, Анатолій Юрійович; Лелека, Сергій Володимирович; Лазарєв, Тарас Валерійович; Деркач, Василь Васильович; Тютюнник, Олексій Володимирович (НТУ "ХПІ", 2017)
Використовуючи розроблену числову модель теплоелектричного стану печі графітування Кастнера, виконано числові дослідження впливу внутрішнього діаметра кільцевих електропрокладок і контактного електричного опору між електродними заготовками на фізичний стан печі прямого нагріву. Запропоновано для збільшення мінімальної температури заготовок впродовж процесу графітування вуглецевої продукції використовувати на кінцях електродних свічок електроконтактні прокладки з підвищеним електричним опором. Раціональним діаметром отвору електроконтактних міжелектродних прокладок є отвір, розміри якого становлять біля 50–70 % від зовнішнього діаметра заготовок.

The numerical research was held to determine possible directions for improvement and modernization of the modern domestic technology of direct graphitization. The influence of the changes in circular gasket internal diameter and contact electrical resistance between electrode artifacts on the state in Castner furnace was investigated. It was found out that the diameter decrease leads to overheating in the central axial part of the electrodes. In turn, the diameter increase leads to significant tempera ture drops. It was also determined that the usage of gaskets with the increased value of electrical resistance during the graphitization process increases the temperature drop in the central artifacts. Based on the obtained results, the following measures to enhance the energetic efficiency of Castner furnaces operation were proposed: the usage of gaskets with the internal diameter, which is 50-70% from the external artifact diameter; the usage of gaskets with the increased value of electrical resistance on the ends of electrode candles. As a material for end electrocontact gaskets, it is possible to use graphite intercalation material with an increased value of electrical resistance, a multilayer structure, which consists of two paired layers of thermo-extended graphite of high and low density, graphite powder, etc. These measures enable to decrease the time for carbon production graphitization, diminish energy expenses and enhance the quality of the electrode products.
Investigation of the influence of constructive-technological parameters on the direct graphitization process of electrodes in Castner furnaces
Keywords: піч графітування Кастнера; електроконтактна прокладка; контактний електричний опір; КЕО; Castner graphitization furnace; electrocontact gasket; contact electrical resistance